The role of the colombian academy of history in the cultural heritage conservation property (2012)
This essays study the emergence of preservation of tangiblecultural heritage in Colombia under the aegis ofhistorians, who in their process of constructing the historyof the nation valued monuments as documents andpromoted their protection. The work of the AcademiaColombiana de Historia (Colombian History Academy)during the first half of the 20th century was decisive inleading to the first legislation about protection and preservationof cultural heritage in Colombia.